The hydraulics of the ILCA plumbing model: A schematic view of ILCA's sub-humid zone research - Kaufmann, Ralph R. von (International Livestock Centre for Africa, 1984)
Presents an overview of ILCA's subhumid zone research programme, outlininig the work conducted at each of the stage concerned with problem analysis, studies of existing systems, field testing of initial interventions, experimentation & modelling.